2014
DOI: 10.1038/ejcn.2014.171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of metabolic processes and body composition on cognitive functions: Nutrition and Dementia Project (NutrDem Project)

Abstract: The global increase in the prevalence of dementia and its associated comorbidities and consequences has stimulated intensive research focused on better understanding of the basic mechanisms and the possibilities to prevent and/or treat cognitive decline or dementia. The etiology of cognitive decline and dementia is very complex and is based upon the interplay of genetic and environmental factors. A growing body of epidemiological evidence has suggested that metabolic syndrome and its components may be importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… 36 Kobayashi et al 37 found that diastolic blood pressure is an independent risk factor affecting the extent of decreased regional cerebral blood flow and is considered an indicator of cognitive impairment. 38 In general, hypertension does not exist alone; it is always accompanied by other risk factors, such as metabolic risks 39 , 40 or stroke-related factors. 41 , 42 Future research should focus on the interaction of multiple risk factors with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Kobayashi et al 37 found that diastolic blood pressure is an independent risk factor affecting the extent of decreased regional cerebral blood flow and is considered an indicator of cognitive impairment. 38 In general, hypertension does not exist alone; it is always accompanied by other risk factors, such as metabolic risks 39 , 40 or stroke-related factors. 41 , 42 Future research should focus on the interaction of multiple risk factors with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…impairments, amnesia, behavioral and neuropsychiatric disorders (10,11) dysphagia, side effects of pharmacotherapy (12), among others, lead to reduced dietary intake and malnutrition. Malnutrition is related to modification of many epigenetic markers, resulting in the development of complex systemic disorders such as diabetes, obesity and hypertension: all related to higher cardiovascular risk and greater progression of AD (13)(14)(15). Malnutrition increases mortality rates in adults with dementia, causes reduced muscle mass, loss of autonomy, increased falls, decubitus ulcers, systemic infections (11) and rapid cognitive decline (16).…”
Section: Nutritional Assessment In Patients With Early-onset Autosomal Dominant Alzheimer's Disease Due To Psen1-e280a Genetic Variant: Amentioning
confidence: 99%